Metabolic Disturbances in Male Broilers of Different Strains. 1. Performance, Mortality, and Right Ventricular Hypertrophy - Gonzales, Elisabeth [UNESP]; Buyse, Johan; Takita, Tânia Sayuri [UNESP]; Sartori, José Roberto [UNESP]; Decuypere, Eddy (My University, 1998)
Two trials were carried out to test the susceptibility for metabolic disturbances of different strains of male broilers. In Trial 1, 1,890 male chickens were allotted in a randomized block design with seven treatments (Arbor Acres, Avian Farms, Cobb-500, Hubbard-Peterson, ISA, Naked Neck, and Ross) and six blocks of 45 chickens. Trial 2 involved 2,184 male chickens of six strains (Arbor Acres, Avian Farms, Cobb 500, Hubbard-Peterson, ISA Naked Neck, and Ross) allotted in seven complete blocks of 52 birds. The same management system was adopted for all birds, reared up to 42 d in an open house during late winter (Trial 1) or late autumn (Trial 2). The most marked differences observed among the strains tested was the lower BW and higher feed conversion of Naked Neck broilers. Total percentage mortalities were high among the most productive broilers, being more than 50% due to sudden death (SDS) and ascites syndrome (AS). No Naked Neck birds died as a consequence of these disturbances and the total mortalities were significantly lower (P ≤ 0.05) than the other strains. The ratio of right ventricle weight to total ventricle weight of the dead birds was over 0.25, except for Naked Neck birds, which presented a nonhypertrophic ratio. The two trials confirmed the relationship between high productivity and high incidence of SDS and AS and indicated that Naked Neck male broilers are resistant to these metabolic disturbances.
Keywords: Ascites syndrome; Broiler; Male; Strains; Sudden death syndrome; animal; animal disease; animal food; ascites; bird disease; breeding; chicken; clinical trial; controlled clinical trial; controlled study; enteritis; female; genetics; heart right ventricle hypertrophy; male; mortality; pathophysiology; physiology; randomized controlled trial; species difference; temperature; weight gain; Animal Feed; Animal Nutrition Physiology; Animals; Ascites; Breeding; Chickens; Enteritis; Female; Hypertrophy, Right Ventricular; Poultry Diseases; Species Specificity; Temperature; Weight Gain